2003
DOI: 10.1295/polymj.35.890
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanical Properties of a Visible Light Curable Urethane Dimethacrylate Based Dental Resin

Abstract: ABSTRACT:The purpose of this study was to evaluate dynamic mechanical properties of urethane dimethacrylate (UDMA) and triethylene glycol dimethacrylate (TEGDMA) based dental resin. Dynamic mechanical properties of a visible light (λ = 400-500 nm) curable UDMA/TEGDMA (70:30 in wt%) resin were investigated for specimens uncured, light-cured for 40 s, and heated to 175• C subsequent to the irradiation for 40 s. Differential scanning calorimetry (DSC)was also employed as a complementary technique. For the light-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
1
1
0
2
Order By: Relevance
“…In the corresponding tan δ versus temperature curve two separate and distinct peaks were observed assigned to two T g s. The trend of two apparent T g values have also been observed in room‐temperature‐cured vinyl ester resins19, 20 and has attributed to additional cure of the sample when the temperature is being scanned in the DMA. Two T g s were also observed in the tan δ curve of UDMA/TEGDMA resin,21 a Bis‐GMA resin,22 a UDMA resin,23 and in two commercial light‐cured resin composites24, 25; in all these cases the two T g s were attributed to the additional thermal cure occurring in the middle of the first glass transition.…”
Section: Resultssupporting
confidence: 91%
“…In the corresponding tan δ versus temperature curve two separate and distinct peaks were observed assigned to two T g s. The trend of two apparent T g values have also been observed in room‐temperature‐cured vinyl ester resins19, 20 and has attributed to additional cure of the sample when the temperature is being scanned in the DMA. Two T g s were also observed in the tan δ curve of UDMA/TEGDMA resin,21 a Bis‐GMA resin,22 a UDMA resin,23 and in two commercial light‐cured resin composites24, 25; in all these cases the two T g s were attributed to the additional thermal cure occurring in the middle of the first glass transition.…”
Section: Resultssupporting
confidence: 91%
“…Indeed, heating increases the segmental mobility of the network and promotes the reaction between the present radicals and the surrounding unreacted functional groups 16. Other studies have shown that, according to differential scanning calorimetry (DSC) analysis, a dimethacrylate sample under a nitrogen atmosphere immediately after photopolymerization exhibits an exothermic reaction effect, whereas heating these samples after 1 night under an air‐free atmosphere has no detectable exothermic effect 17, 18…”
Section: Introductionmentioning
confidence: 99%
“…Η περιοχή μείωσης του logE΄ στο θερμοκρασιακό εύρος 85 -175 o C Στην καμπύλη της μεταβολής του μέτρου απωλειών, Ε΄΄, με τη θερμοκρασία για όλα τα υλικά, εμφανίζονται δύο ευρείες κορυφές. Η πρώτη κορυφή είναι το αποτέλεσμα της διαδικασίας χαλάρωσης του φωτοσκληρυμένου σύνθετου υλικού, ενώ η δεύτερη κορυφή συνιστά τη διαδικασία χαλάρωσης του υλικού που προέκυψε από την επιπρόσθετη θερμική σκλήρυνση του φωτοσκληρυμένου υλικού.Στην καμπύλη της μεταβολής της tanδ ως προς τη θερμοκρασία, σε όλα τα υλικά, δυο ξεχωριστές και σαφής κορυφές παρατηρηθήκαν (Σχήμα 7.14.γ) 69,132,[170][171][172][173][174]. Κάθε κορυφή αντιστοιχεί σε καθεμιά από τις απότομες πτώσεις της καμπύλης του Ε΄ με τη θερμοκρασία, που αντιπροσωπεύουν τις δύο περιοχές της υαλώδους μετάβασης.…”
unclassified